2022
DOI: 10.21203/rs.3.rs-1837156/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Papillomavirus 16 E6 Promotes Angiogenesis of Lung Cancer by SNHG1

Abstract: Human papillomavirus (HPV) is a risk factor for lung cancer. However, the mechanisms underlying is not known. Long noncoding RNAs (lncRNAs) have been found to play an important part in the occurrence and development of lung cancer due to their particular characteristics. HPV induced lung carcinogenesis are incompletely defined. We aim to screen and clarify the functions of lncRNAs that are differentially expressed in HPV related lung cancer. We find that lncRNA SNHG1 is upregulated in lung cancer cells infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results of this study contradict some previous reports on the association between HPV infection and lung cancer. A study by NIE Z et al suggests that HPV16 infection may influence the development of lung cancer, particularly by regulating the SNHG1 gene and promoting angiogenesis, which is crucial for tumor growth and spread [47] . A study involving 152 cases of primary lung cancer patients as the lung cancer group and 87 individuals with benign lung lesions as the control group revealed that the incidence of HPV infection in primary lung cancer patients was higher than in those with benign lung lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study contradict some previous reports on the association between HPV infection and lung cancer. A study by NIE Z et al suggests that HPV16 infection may influence the development of lung cancer, particularly by regulating the SNHG1 gene and promoting angiogenesis, which is crucial for tumor growth and spread [47] . A study involving 152 cases of primary lung cancer patients as the lung cancer group and 87 individuals with benign lung lesions as the control group revealed that the incidence of HPV infection in primary lung cancer patients was higher than in those with benign lung lesions.…”
Section: Discussionmentioning
confidence: 99%